Why do we need the particle “not”: evolution of semantic structures and propositional attitudes - Raisa E. Barash; Alexander Yu. Antonovskiy (Слово.ру: балтийский акцент, 2022)
The article investigates the problem of the universally significant meaning of communicative messages. This framework problem implies answering more specific questions — is there a reality (correlative to the meaning of judgments) that would guarantee the universality of the meanings of linguistic expressions; is there a reality behind moralizing or judgments of taste that ensures agreement on value judgments if they become the content of communication. What provides the typical identity of mental states (thoughts, perceptions, representations, sensations) in different individuals, when these states are thematized in communication? Is there a typical correlation behind them in reality, which ensures the identity of mental states? The article posits that propositional attitudes act as “carriers” or frameworks of typical communicative environments, indirect contexts in which propositional content are localized as the main — intralingual — evolutionary mechanism that stabilizes key communicative meanings. Indirect contexts produced in the language or the operators “I know that...”, “I hope that...”, “I remember that...”, “I want that…”, “I imagine that...” protect sentences from negation and make it possible to reproduce universally significant meanings.